DIGITALISASI MANAJEMEN USAHA DAN PEMASARAN UNTUK MENINGKATKAN KINERJA UMKM RUSMY ROSE TEH BUNGA TELANG - Joko Dwi Mulyanto; Ina Maryani; Suripah Suripah; Nisrina Lukluk'il Numa; Naufal Haidar Azhar (Universitas Mataram, 2026)
Rusmy Rose Teh Bunga Telang UMKM has potential in herbal products but faces serious obstacles in management and marketing. The business management system, particularly financial and stock recording, is still done manually and is unstructured. In addition, marketing activities are very limited to offline sales and do not utilize digital platforms, resulting in stagnant turnover and a narrow market reach. This community service activity aims to digitize business management and marketing to improve the performance and competitiveness of MSMEs. The method used is participatory empowerment. The activity was carried out in three main stages: assessment (FGD), training (digital management, branding, e-commerce, AI), and technology implementation assistance. The results of the activity showed significant changes in the partners. In terms of management, partners have implemented digital financial and stock records using Google Sheets. In terms of marketing, partners now have and manage e-commerce accounts (Shopee, Tokopedia) and websites. Partners are also able to produce independent promotional content using Canva and AI. The main impact is an increase in average monthly sales turnover of 20-30%. Additionally, the market reach has been successfully expanded to new areas such as Purbalingga, Banjarnegara, and Cilacap. It is concluded that comprehensive digitalization of management and marketing has proven effective in improving the performance and competitiveness of Rusmy Rose UMKM